2016
DOI: 10.1007/s13197-016-2172-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed electric field (PEF) treatment on sugarcane juice

Abstract: This study was carried out to evaluate the effect of PEF process using static treatment chamber on fresh sugarcane juice with and without addition of lemon and ginger with respect to microbial content, chemical properties, nutrient content and shelf life extention of the product. The fresh sugar cane juice without addition of lemon and ginger treated at different field strengths (30 kV cm −1 and 50 kV cm −1) and different pulse numbers (150, 300) was initially investigated by storage at room temperature (31°C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 12 publications
3
37
0
1
Order By: Relevance
“…According to Huang, Tian, Gai, and Wang (2012), inactivation of microorganisms during PEF treatment is due to the cell membrane collapse and changed the cell structure and morphology, the effects on endogenous vital enzymes associated with the cell metabolism, change in gene expression and damage to cellular genetic material. Earlier, the reduction in microbial load after PEF treatment was reported by Kayalvizhi, Pushpa, Sangeetha, and Antony (2016) in sugarcane juice. Zhang et al.…”
Section: Resultsmentioning
confidence: 69%
“…According to Huang, Tian, Gai, and Wang (2012), inactivation of microorganisms during PEF treatment is due to the cell membrane collapse and changed the cell structure and morphology, the effects on endogenous vital enzymes associated with the cell metabolism, change in gene expression and damage to cellular genetic material. Earlier, the reduction in microbial load after PEF treatment was reported by Kayalvizhi, Pushpa, Sangeetha, and Antony (2016) in sugarcane juice. Zhang et al.…”
Section: Resultsmentioning
confidence: 69%
“…Kayalvizhi et al reported pH values in the range of 3.98 to 5.10. For soluble solids, the results were between 17 and 17.5 °Brix.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that with increasing the electric field intensity, the inactivation of microorganisms in orange juice is more (Gurtler et al, ). Kayalvizhi, Pushpa, Sangeetha, and Antony () in a study investigated the effect of pulsed electric field on microbial content, chemical properties, nutrients, and a shelf life of the product in fresh sugarcane juice. At the end of applying the pulsed electric field, consistency in the quality of the product compared to untreated samples was reported and also microorganisms were significantly reduced.…”
Section: Resultsmentioning
confidence: 99%